Yard phytoarchitecture for onsite sanitation of household wastewater containing copper - Samudro, Ganjar; Samudro, Harida; Mangkoedihardjo, Sarwoko (International Journal of Advances in Applied Sciences, 2024)
Copper can be found in various equipment, building materials, and consumer products. When buildings are used, copper can enter wastewater in different ways. It is challenging for occupants to remove copper physically or chemically since they can potentially reduce copper levels through yard phytoarchitecture. This study aims to formulate houseplants' suitability to become decorative plants for the yard phytoarchitecture, simultaneously as onsite sanitation. This study identified the copper deconcentration pathway in wastewater by studying published works-based research. Literature was collected and selected based on recency, accessibility, and the relationship among copper, wastewater, and plants. The study findings show that processing copper by plant has the greatest opportunity to be implemented on a building scale. The yard phytoarchitecture system involves arranging plants in the yard, which serves both as a decorative feature and a way to treat the building's wastewater. It can be used on dry yards or ponds and only requires a small amount of land. The plants used should have low leaf density and high root density. It plays a dual role consisting of onsite sanitation infrastructure and yard aesthetics, which mutually strengthen the environmental health locally and positively effect on a larger scale.